2015
DOI: 10.1021/acs.jpca.5b00509
|View full text |Cite
|
Sign up to set email alerts
|

Energy Pooling Upconversion in Organic Molecular Systems

Abstract: A combination of molecular quantum electrodynamics, perturbation theory, and ab initio calculations was used to create a computational methodology capable of estimating the rate of 3-body singlet upconversion in organic molecular assemblies. The approach was applied to quantify the conditions under which such relaxation rates, known as energy pooling, become meaningful for two test systems: stilbene-fluorescein and hexabenzocoronene-oligothiophene. Both exhibit low intra-molecular conversion but inter-molecula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 29 publications
0
26
0
4
Order By: Relevance
“…Incorporating the experimental results above into existing analyses of the CEP15 and 2PA (ref. 32) processes suggests guidelines for optimizing the selection of sensitizer and acceptor chromophores to maximize the CEP rate ( k CEP ), as follows: The acceptor should have a large 2PA cross-section () as well as minimal FRET losses to the sensitizers, and it should exhibit minimal self-quenching in the solid state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporating the experimental results above into existing analyses of the CEP15 and 2PA (ref. 32) processes suggests guidelines for optimizing the selection of sensitizer and acceptor chromophores to maximize the CEP rate ( k CEP ), as follows: The acceptor should have a large 2PA cross-section () as well as minimal FRET losses to the sensitizers, and it should exhibit minimal self-quenching in the solid state.…”
Section: Discussionmentioning
confidence: 99%
“…CEP is the process of two photoexcited sensitizer chromophores non-radiatively transferring their energy to a single higher-energy state in an acceptor chromophore. Instead of dipole–dipole coupling between the emissive states of the sensitizers and the absorbing state of the acceptor, as in the Förster resonance energy transfer process (FRET), CEP is carried out via a coupling of the emissive states of both sensitizers with the two-photon absorption (2PA) tensor of the acceptor131415. In this way the sensitizers act as photon storage centres that relax the stringent temporal and spatial constraints for achieving 2PA in the acceptor, enabling upconversion with greater efficiency and at reduced excitation intensities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RET, ETU and EP are all based on the same dipole coupling tensor, and donor-acceptor separation sensitivity dwells exclusively there for each process 5,26 . For the RET and ETU, the rate is proportional to the square of the coupling tensor while the EP rate is proportional to its fourth power.…”
Section: Methodsmentioning
confidence: 99%
“…In recent work 5 we have developed a framework of quantum electrodynamics (QED) 6,7 to address Raman scattering influenced by a second, neighboring molecule; this is one of many situations in which such a theory of fundamental coupling is applied. [8][9][10][11][12][13][14][15][16] Our interest is not only in the modification of line intensities (beyond the familiar heterogeneous spectral broadening): we have shown that it is possible to engender additional spectra lines that are not conventionally Raman active, identifying the constraints that apply. The symmetry aspects of the latter feature are the focus of the present work.…”
Section: Introductionmentioning
confidence: 99%